Nonsurgical Endodontic Treatment of Type II Dens Invaginatus in A Maxillary Lateral Incisor: A Case Report - Isaltino, Marina da Cunha; Oliveira , Natália Gomes de; de Melo Júnior, Paulo Maurício Reis; Lyra, Carolina Viana Vasco; Fernandes, Pedro Henrique de Freitas; de Albuquerque, Diana Santana (Iranian Endodontic Journal, 2024)
Dens invaginatus (DI) is one of the developmental dental anomalies that results in an invagination of the enamel organ into the dental papila during odontogenesis. The purpose of this study is to report a case of nonsurgical endodontic treatment of an Oehlers type II DI in a right maxillary lateral incisor with an extensive periapical damage, along with the two-year clinical and tomographic follow-up. A 30-year-old patient was referred for endodontic treatment of tooth #12. On clinical examination, a change in the shape and color of the crown was observed. The tooth responded negative to pulp sensibility, percussion, palpation and mobility tests. After tomographic evaluation, an Oehlers type II DI was visualized, in addition to an extensive periradicular lesion. The diagnosis was asymptomatic apical periodontitis. The treatment was carried out in two sessions, through intense enhancement of the auxiliary chemical substance with passive ultrasonic irrigation, XP-Endo Finisher and the use of hydroxide-based intracanal medication. Appropriate treatment in cases with anatomic variations requires an accurate and early diagnosis based on clinical examination and radiographic images. A two-year follow-up of the present case showed that the correct diagnosis associated with appropriate instrumentation techniques, supplementary disinfection, and adequate three-dimensional sealing of the canal with filling material, resulted in regression of the periradicular lesion and bone repair.